All-Stars and Movie Stars : Sports in Film and History. - Briley, Ron (Film and History., 2015)
In addition to the thrill of victory and the agony of defeat, sports offer a versatile arena for discussion of class, race, gender, sexuality, and other social facets. All-Stars and Movie Stars: Sports in Film and History examines the interplay between sports films and the defining characteristics of the cultures from which they emerge. This important and unique collection will serve scholars of film, popular culture, and American history.